Technology-Mediated Language Training: Developing and Assessing a Module for a Blended Curriculum for Newcomers - McLellan, Gillian; Kartchava, Eva; Rodgers, Michael (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
Newcomers to Canada with low proficiency in English or French often face challenges in the workforce (Kustec, 2012). While language classes provide workplace language training, not all newcomers are able to attend face-to-face classes (Shaffir & Satzewich 2010), suggesting a need for outside the classroom, occupation-specific language training. The use of technology has been shown to be advantageous for second language (L2) learning (Stockwell, 2007), especially when used outside the classroom (i.e., mobile-assisted language learning), as mobile technology affords learners greater control and flexibility over their own learning (Yang, 2013). This paper reports on a study investigating the development of a blended curriculum for L2 learners employed in customer service. A technology-mediated module was designed and developed within a task-based language teaching framework to provide workplace-linguistic support on mobile devices, enabling learners to access the language instruction they needed, when they needed it. The module contents and usability were assessed by high-beginner English proficiency newcomers employed in customer service (n=4) and their volunteer teachers (n=4). Results confirm the overall benefits of using language learning technology in providing instruction that meets participant language needs, ensuring opportunities for individualized training. Implications for designing, implementing, and researching technology-mediated modules are discussed.